ISOLASI DAN IDENTIFIKASI SENYAWA TOKSIK PADA EKSTRAK METANOL DAUN GAHARU (Gyrinops versteegii) - Mika Adi Santosa, I Nyoman; Raka Astiti Asih, Ida Ayu; Mayun Laksmiwati, A. A. I. A. (Jurnal Kimia (Journal of Chemistry), 2013)
Isolation and identification of toxic compound from methanol extract of eaglewood leaves ( Gyrinops versteegii ) has been done. Extraction of 869 g of dried eaglewood leaves powder produced concentrated extracts of n -hexane (21.56 g) and methanol (81.85 g). The result of toxicity test for both of concentrated extracts showed methanol extract was the most toxic with LC 50 of 39.81 ppm. Partition of methanol extract gained three concentrated extracts in chloroform (2.74 g) , ethyl acetate (3.44 g) and water (15.56 g). The result of toxicity test showed chloroform extract was the most toxic with LC 50 of 23.44 ppm. Chloroform extract was then separated and purified by chromatography technique and obtained three toxic fractions namely fraction  of A (0.44 g), B (0.22 g) and C (0.13 g). The toxicity test showed that fraction C was the most toxic with LC 50 of 34.67 ppm. The phytochemical test result showed that fraction C was belong to triterpene groups. Analysis using UV-Vis spectrophotometer gained 2 peaks at ? 245 nm and ? 416 nm, showing the possibility of the chromophore C=O and C=C, respectively. Analysis using infrared spectrophotometer showed the characteristic absorption of an -OH group, aliphatic CH, C=O and C=C on wave numbers of cm -1 3441.01; 2924.09 (-CH 3 ) and 2854.65 (-CH 2 ); 1743.65; and 1627.92, respectively. According to phytochemical test and spectrophotometry analysis, the isolate of fraction C was supposed to contain triterpene group compounds which has functional groups of OH, aliphatic CH, C=O and C=C.
Keywords: isolation, identification, Artemia salina Leach, Cordyline terminalis Kunth, Liliaceae